Impact of pre-stroke dependency on outcome after endovascular therapy in acute ischemic stroke - Oesch, Lisa; Arnold, Marcel; Bernasconi, Corrado; Kaesmacher, Johannes; Fischer, Urs; Mosimann, Pascal J.; Jung, Simon; Meinel, Thomas; Goeldlin, Martina; Heldner, Mirjam; Volbers, Bastian; Gralla, Jan; et al. (Journal of Neurology, 2020)
Background and purpose Current demographic changes indicate that more people will be care-dependent due to increasing life expectancy. Little is known about impact of preexisting dependency on stroke outcome after endovascular treatment (EVT).
CRIS-Team WoS Importer:2020-09-18